Reading as an Access to Mathematics Problem Solving on Multiple-Choice Tests for Sixth-Grade Students - Helwig, Robert; Rozek-tedesco, Marick A.; Tindal, Gerald; Heath, Bill; Almond, Patricia J. (The Journal of Educational Research, 1999)
The effect of providing middle school students with a video accommodation for a standardized mathematics test was examined. Two hundred forty-seven students were asked to solve 60 word problems. One half of the questions were presented in standard form, while the other half were read by an actor on a video monitor. Students were grouped according to mathematics and reading ability. A test accommodation effect was found for students possessing below-average mathematics skills. The problems were identified as having relatively high reading difficulty according to word count, number of verbs, and word familiarity. Students with above-average mathematics proficiency but low reading skill performed better when the questions were presented in video format. This accommodation may be useful on specific test items for students with certain reading deficiencies.

Whose Reality Counts?: Putting the first last - Chambers, Robert (Practical Action Publishing, 1999)
In this sequel to Rural Development: Putting the last first Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power. Through analysing experience - of past mistakes and myths, and of the continuing methodological revolution of PRA (participatory rural appraisal) - the author points towards solutions. In many countries, urban and rural people alike have shown an astonishing ability to express and analyse their local, complex and diverse realities which are often at odds with the top-down realities imposed by professionals. The author argues that personal, professional and institutional change is essential if the realities of the poor are to receive greater recognition. Whose Reality Counts? presents a radical challenge to all concerned with development, whether practitioners, researchers or policy-makers, in all organizations and disciplines, and at all levels from fieldworkers to the heads of agencies.This is a thought-provoking book and it would interest all those concerned with the realities of the poor in the developing world.

The impact of coaching in South African primary science InSET - Harvey, Stephen (International Journal of Educational Development, 1999)
This article presents evidence from an evaluation conducted by the Primary Science Programme (PSP) in South Africa, concerning the impact of classroom-based coaching on the teaching methods used by primary science teachers. The methods used by teachers provided with both workshops and classroom-based coaching were compared with those used by teachers who received workshops only and a control group who received no InSET at all. The findings showed that teachers who received coaching made substantial changes, whereas most teachers who received workshops-only remained similar to the control group. A social constructivist approach is adopted in interpreting these findings. The implications of this study for designing effective InSET in developing countries are also discussed.
Keywords: Constructivism; In-service training; Leader teachers; Primary science; South Africa; Teacher education

Supporting untrained teachers in Malawi - Kunje, Demis; Stuart, Janet (International Journal of Educational Development, 1999)
In the aftermath of the introduction of free primary education in Malawi, 17 000 untrained teachers were recruited to meet the new demand for schooling. This article reports a study carried out to investigate how the new recruits were coping and how far the schools were able to provide informal on-the-job training. It also describes how action research was introduced to help heads and both qualified and unqualified teachers to improve their own practice. Conclusions are drawn about the feasibility of school-based training in Malawi.

Home Computers and School Performance - Attewell, Paul; Battle, Juan (The Information Society, 1999)

Applying Systems Design Principles to the Design of Web-Based Training Systems - Bettin, Antje; Dillinger, Lisa; Ferraro, Sal; St-Pierre, Armand (WebNet Journal: Internet Technologies, Applications & Issues, 1999)
The Web is a popular platform for training educators and learners in educational systems. We find several Web-based training systems that are developed by enterprises that try to train teachers and students to use Web technologies in educational settings. The purpose of this article is to apply systems design principles to the design of Web-based training systems for teachers and learners. Several issues will be addressed in this paper such as the development of an Integrated Learning Community System (ILCS) for a better learning environment, the Quality Assurance / Audience Analysis /...
Keywords: ⛔ No DOI found

Complexity and post-modernism: Understanding complex systems - Cilliers, Paul; Spurrett, David (South African Journal of Philosophy, 1999)
Keywords: ❓ Multiple DOI

Research framework and dimensions for evaluating the effectiveness of educational technology systems on learning outcomes - Jones, Trevor H.; Rocco, Paolucci (Journal of Research on Computing in Education, 1999)
Keywords: ❓ Multiple DOI

Form and Substance in Mathematics and Science Professional Development - Kennedy, Mary M (National Institute for Science Education, University of Wisconsin-Madison, 1999)
This document reviews studies of professional development for teachers to examine benefits to students in science and mathematics education. A major finding from this review was that programs that focused on teaching classroom management strategies or attaining knowledge of how students learn specific school subject matter provided later benefits to students. The more successful professional development programs were not simply courses in mathematics or science, but instead were about what to teach and how students learn that subject matter.

Introduction to systems thinking - Kim, Daniel H. (Pegasus Communications Waltham, MA, 1999)

Human Development in Asia 1999: The Crisis of Governance - Mahbub ul Haq Human Development Centre (Human development in South Asia, 1999)

Needs-based resource allocation in education: via formula funding of schools - Ross, Kenneth N.; Levačić, Rosalind; International Institute for Educational Planning (UNESCO, International Institute for Educational Planning, 1999)
Keywords: Allocation Education; Education; Education and state; Finance

The impact of education technology on student achievement: What the most current research has to say. - Schacter, John (1999)
Keywords: ⛔ No DOI found

The new dynamics of strategy - Snowden, David (IBM Systems Journal, 1999)
The new dynamics of strategy
Keywords: ⛔ No DOI found

Gender differences in parental investment in education - Alderman, Harold; King, Elizabeth M. (Structural Change and Economic Dynamics, 1998)
The gender gap in schooling is puzzling given that the expected returns to an individual for increased schooling — as measured by proportional wage increments — does not differ by gender. This paper explores possible explanations for the disparity using a model of parental investment in children. The model allows for differences in investments due to differences in costs — including the opportunity cost of the child's labor as well as school fees and availability. Moreover, it indicates that disparities in investment could come through differences in returns realized by parents, for example, in the probability of transfers from children to parents or in the degree of sympathy or altruism, even when market returns to the children themselves do not differ. While it is difficult to distinguish these different explanations empirically, the paper reviews available evidence and indicates interventions that governments can make to reduce the gender gap in education.
Keywords: Gender disparities; Schooling investments

Mixed Methodology: Combining Qualitative and Quantitative Approaches - Tashakkori, Abbas; Teddlie, Charles (SAGE, 1998)
Looking for a practical guide to using mixed methodologies? This book explores the most effective way to combine qualitative and quantitative techniques. It begins with a discussion of the paradigm wars between positivism and constructivism, explains the difference between using mixed methods in just the research methodology portion of a study versus using mixed model studies across all phases of the process, and then presents a typology of mixed methods and mixed model studies.
Keywords: Social Science / Research

Assessment and classroom learning - Black, Paul; Wiliam, Dylan (Assessment in Education: Principles, Policy & Practice, 1998)

Complexity theory and the social sciences: An introduction - Byrne, David S. (Psychology Press, 1998)

Learning circles: creating conditions for professional development - Collay, Michelle (Corwin Press, 1998)
Keywords: Cooperativeness; Group work in education; In-service training; Teachers; Teaching; United States

Children's Online Privacy Protection Rule ("COPPA") - COPPA (Federal Trade Commission, 1998)
COPPA imposes certain requirements on operators of websites or online services directed to children under 13 years of age, and on operators of other websites or online services that have actual knowledge that they are collecting personal information online from a child under 13 years of age.

Quality assessment tool for quantitative studies - Effective Public Health Practice Project (Effective Public Health Practice Project, 1998)
The “Quality Assessment Tool for Quantitative Studies” developed by the Effective Public Health Practice Project (EPHPP) is a tool for doing knowledge synthesis. This instrument, along with a user manual, provides a standardized means to assess study quality and develop recommendations for study findings. The quality appraisal tool was developed by the Effective Public Health Practice Project (EPHPP) as a discrete step within the systematic review process.
Keywords: Reviewed

Activists Beyond Borders: Advocacy Networks in International Politics - Keck, Margeret E.; Sikkink, Kathryn (Cornell University Press, 1998)
Margaret E. Keck and Kathryn Sikkink — Activists Beyond Borders: Advocacy Networks in International Politics

Systems theories: Their origins, foundations, and development - Laszlo, Alexander; Krippner, Stanley (ADVANCES IN PSYCHOLOGY-AMSTERDAM-, 1998)

Voluntary and involuntary minorities: A cultural-ecological theory of school performance with some implications for education - Ogbu, John U.; Simons, Herbert D. (Anthropology & Education Quarterly, 1998)

Inservice Training of Primary Teachers through Interactive Video Technology: An Indian Experience - Raina, V. K.; Maheshwari, A. N. (International Review of Education, 1998)
Discusses India's Special Orientation Programme for Primary School Teachers (SOPT), a new technology used to train large numbers of teachers so that the losses in transmission inherent in the "cascade model" are avoided. Responses from teachers and trainers show there is considerable potential for the exploitation of this technology. Contains 20 references. (VWC)

A contemporary approach to public expenditure management - Schick, Allen (1998)
A contemporary approach to public expenditure management (English)

An integrated technology adoption and diffusion model - Sherry, Lorraine (International Journal of Educational Telecommunications, 1998)
Keywords: ⛔ No DOI found

When Mother-tongue Education is not Preferred - Gupta, Anthea Fraser (Journal of Multilingual and Multicultural Development, 1997)
In some language situations primary education in the mother tongue may not be desirable. A number of factors may militate against education in the mother tongue: (1) difficulty in determining the mother tongue. This is especially a problem in multilingual settings where children grow up with multiple mother tongues; (2) definition of 'a language'. Mother tongues may be deemed to be the standard variety; and (3) social and ethnic divisiveness of mother tongue education. In multilingual settings the maintenance of social cohesiveness may be of more importance than the benefitof mother-tongue education.Where patterns of language use are linked to social class, mother-tongue education could further diminish access to power structures by underprivileged groups. Ideological issues can be resolved only in the context of the particular social and political situation. There is no general rule that primary education should be in the mother tongue.

An interactive system for finding complementary literatures: a stimulus to scientific discovery - Swanson, DR; Smalheiser, NR (Artificial Intelligence, 1997)
An unintended consequence of specialization in science is poor communication across specialties. Information developed in one area of research may be of value in another without anyone becoming aware of the fact. We describe and evaluate interactive software and database search strategies that facilitate the discovery of previously unknown cross specialty information of scientific interest. The user begins by searching MEDLINE for article titles that identify a problem or topic of interest. From downloaded titles the software constructs input for additional database searches and produces a series of heuristic aids that help the user select a second set of articles complementary to the first set and from a different area of research. The two sets are complementary if together they can reveal new useful information that cannot be inferred from either set alone. The software output further helps the user identify the new information and derive from it a novel testable hypothesis. We report several successful tests and applications of the system.
Keywords: _Added-ailr-2024

Designing for or designing with? Informant design for interactive learning environments - Scaife, Michael; Rogers, Yvonne; Aldrich, Frances; Davies, Matt (Association for Computing Machinery, 1997)
Keywords: children; design; hi-tech; informant; interactive learning environments; low-tech; prototypes

General System Theory and the Ecosystem Concept (The Bulletin of the Ecological Society of America, 1997)
Keywords: ⚠️ Invalid DOI

Interactive Radio Instruction: Twenty-Three Years of Improving Educational Quality - Bosch, Andrea (Education and Technology Technical Notes Series, 1997)
Interactive Radio Instruction (IRI) is the use of interactive lessons delivered through either radio broadcast or audiocassette. An "audio" teacher directs the lessons while classroom teachers serve as facilitators. IRI has been used in developing countries worldwide to improve the quality of education across a range of school subjects and to serve as a form of teacher development. Multiple studies of IRI consistently have shown high learning gains, decreased equity gaps, and cost-effectiveness. Twenty-three years after their initial launch, several major IRI projects continue to operate successfully. While over the years IRI has been updated in various ways, its basic structure and methodology remain largely unaltered. IRI continues to be used in projects around the world.
Keywords: ___working_potential_duplicate

The Culture of Education - Bruner, Jerome (Harvard University Press, 1997)
In a masterly commentary on the possibilities of education, eminent psychologist Jerome Bruner reveals how education can usher children into their culture, though it often fails to do so. Going well beyond his earlier acclaimed books on education, Bruner looks past the issue of achieving individual competence to the question of how education equips individuals to participate in the culture on which life and livelihood depend.

Langues africaines: vers une édition scolaire: à propos d'un programme de formation pour auteurs de manuels scolaires - Chatry-Komarek, Marie (Langues africaines, 1997)
Keywords: ⛔ No DOI found

Brave new schools: Challenging cultural illiteracy through global learning networks - Cummins, Jim; Sayers, Dennis (Palgrave Macmillan, 1997)

Dynamics and indeterminism in developmental and social processes - Fogel, Alan; Lyra, Maria CDP; Valsiner, Jaan (Psychology Press, 1997)

Discrimination in education: the Tanzania case - Kisanga, Maria E; Katunzi, Naomi (UNESCO, 1997)

The Role of Educational Technology in Upgrading Teacher Education in Pakistan - Abbasi, M. Hashim; Millar, Alex C. (1996)
This paper outlines a joint Asian Bank/Pakistan Ministry of Education project designed to upgrade the state of teacher education and to improve the quality, status, and professional self-esteem of Pakistan's teachers. The main strategies identified by the Project for priority attention include: structural changes through the creation of four new types of teacher education institutions in each of the provinces; development of the main teacher education pre- and in-service courses; increased output and improved standard of teachers at all levels; development and implementation of a Total Educational Technology Plan; and upgrading and strengthening of existing Government Colleges for Elementary Teachers and Government Colleges of Education. Educational technology is a key element designed to assist in achieving the Project's major goals and objectives. Needs analysis produced recommendations geared for: target population; new teacher education courses; allocation of electronic media; teacher/principal attitudes towards the equipment and software; potential sources of software; availability of ancillary funding; specialist educational technology assistance for teachers; developing a profession of educational technology interested people; storage and access for hardware and software; roles of Mobile Training Units; and overseas lessons on the application of educational technology. (AEF)
Keywords: Educational Change; Educational Development; Educational Finance; Educational Strategies; Educational Technology; Elementary Secondary Education; Foreign Countries; Higher Education; Needs Assessment; Professional Development; Program Improvement; Resource Allocation; Schools of Education; Teacher Attitudes; Teacher Education; Technology Planning

The Effects of Summer Vacation on Achievement Test Scores: A Narrative and Meta-Analytic Review - Cooper, Harris; Nye, Barbara; Charlton, Kelly; Lindsay, James; Greathouse, Scott (Review of Educational Research, 1996)

Development of an aspect of executive control: Development of the abilities to remember what I said and to “Do as I say, not as I do” - Diamond, Adele; Taylor, Colleen (Developmental Psychobiology, 1996)
Luria's tapping test (tap once when E taps twice, tap twice when E taps once) was administered to 160 children (80 males, 80 females) between 31/2 to 7 years old. Older children were faster and more accurate than younger children, with most of the improvement occurring by the age of 6. All children tested demonstrated understanding of the instructions during the pretest, and most started out performing well, but younger subjects could not sustain this. Over the 16 trials, percentage of correct responses decreased, especially among younger subjects. Performance here was compared with performance on the day-night Stroop-like task. The most common error on both tasks was to comply with only one of the two rules. Other errors included tapping many times regardless of what the experimenter did and doing the same thing as the experimenter, rather than the opposite. It is suggested that the tapping task requires both the ability to hold two rules in mind and the ability to inhibit a strong response tendency, that these abilities improve between 3–6 years of age, and that this improvement may reflect important changes within frontal cortex during this period of life. © 1996 John Wiley & Sons, Inc.

Instructional Technology: A Tool or a Panacea? - Kimmel, Howard; Deek, Fadi (Journal of Science Education and Technology, 1996)
It is time to recognize that educational technology cannot be considered a panacea for educational reform. Technology, when properly used, can be a very effective tool for improving and enhancing instruction and learning experiences in the content areas. However, incorporation of electronic tools, such as computers and videodiscs, into classrooms must be accompanied by systemic change in the educational process. Successful utilization of technology depends on how we provide teachers with the necessary environment for training, tools for instruction, and technology evaluation skills. This paper examines some of the misuses of technology and then explores the appropriate use of technology in the context of current educational reform. The focus is on the integration of technology in the educational process that provides a learning environment allowing discovery and creativity through the use of computer visualizations. The teacher is seen as the essential element, requiring a solid foundation in the general applications of technology, and the ability to evaluate and select systems that are effective and efficient for specific applications.

Technology and Distance Education: Sharing Experience in Sindh, Pakistan - Panhwar, Farzana (1996)
Female literacy in Pakistan is among the lowest in the world. In 1981, the literacy rate was 16 percent for females, and 7.3 percent for rural women. Distance education can effect many social changes. Females would be the main beneficiaries because it is not socially acceptable for girls to leave home for education; parents do not like coeducational schools; social attitudes do not permit school education for girls on the conviction that any freedom to go out will result in sexual involvement with males; and women with low levels of education are stigmatized and accorded low social status. Both rural and urban conditions can be improved by providing women with integrated programs in hygiene, food, health, and basic and vocational education, as well as professional training in the sciences, trades, and industry. Problems with Pakistan's distance education system include the lack of opportunity for question and answer sessions; no provision to make up missed classes; absence of teachers to advise students on the use of the materials; lack of competition; lack of competent teachers; corruption and poor funding, resulting in nonavailability of materials in libraries; low standards, resulting in receipt of degrees without corresponding learning; lack of facilities for lab work in science and technical training; lack of rights to duplicate costly foreign video materials. (TD)
Keywords: Access to Education; Distance Education; Educational Needs; Elementary Secondary Education; Foreign Countries; Illiteracy; Relevance (Education); Rural Women; Sex Discrimination; Social Attitudes; Vocational Education; Womens Education

Five technologies for educational change: Systems thinking, systems design, quality science, change management, instructional technology - Salisbury, David F. (Educational Technology, 1996)

Teacher change in technology-rich classrooms - Sandholtz, Judith H.; Ringstaff, Cathy (Education and technology: Reflections on computing in classrooms, 1996)
Keywords: ⛔ No DOI found

Systems thinking - Senge, Peter (Executive Excellence, 1996)
Keywords: ⛔ No DOI found

What is curriculum? Exploring theory and practice - Smith, Mark K (the encyclopaedia of informal education, 1996)

Understanding of consumer behaviour as a prerequisite for environmental protection - Ölander, Folke; Thøgersen, John (Journal of Consumer Policy, 1995)

National Education Act 1997 (amendment) - United Republic of Tanzania (No. 10 of 1995, 1995)

Basic Concepts and Techniques of Rapid Appraisal - Beebe, James (Human Organization, 1995)

The Evolution of Constructivist Learning Environments: Immersion in Distributed, Virtual Worlds - Dede, Chris (Educational Technology, 1995)
Keywords: ⛔ No DOI found

Technology integration: Managing technological evolution in a complex environment - Iansiti, Marco (Research policy, 1995)

Documentation of educational research in Pakistan, 1947-1995: an annotated bibliography - Shabab, M. H (Academy of Educational Planning and Management, 1995)

A how to guide to reflection: Adding cognitive learning to community service programs - Silcox, H. C. (Brighton Press, 1995)

Grounded theory methodology: An overview - Strauss, A.; Corbin, J. (Handbook of qualitative research, 1995)
Keywords: ___working_potential_duplicate; auto_merged

Nothing as practical as good theory: Exploring theory-based evaluation for comprehensive community initiatives for children and families - Weiss, Carol H. (New approaches to evaluating community initiatives: Concepts, methods, and contexts, 1995)
Keywords: ⛔ No DOI found

The relationship between cognition and action: performance of children 312–7 years old on a stroop- like day-night test - Gerstadt, Cherie L.; Hong, Yoon Joo; Diamond, Adele (Cognition, 1994)
One hundred and sixty children 312–7 years of age (10M, 10F at each 6-month interval) were tested on a task that requires inhibitory control of action plus learning and remembering two rules. They were asked to say “day” whenever a black card with the moon and stars appeared and to say “night” when shown a white card with a bright sun. Children <5 years had great difficulty. They started out performing well, but could not sustain this over the course of the 16-trial session. Response latency decreased from 312 to 412 years. Children <412 years performed well when they took very long to respond. To test whether the requirement to learn and remember two rules alone was sufficient to cause children difficulty, 80 children 312–5 years old were tested on a control version of the task (“say ‘day’ to one abstract design and ‘night’ to another”). Even the youngest children performed at a high level. We conclude that the requirement to learn and remember two rules is not in itself sufficient to account for the poor performance of the younger children in the experimental condition.

Ecological models of human development - Bronfenbrenner, Urie (Readings on the development of children, 1994)
Keywords: ⛔ No DOI found

Des manuels scolaires sur mesure: Guide pratique à l'intention des auteurs de manuels scolaires - Chatry-Komarek, Marie (Des manuels scolaires sur mesure, 1994)
Keywords: ⛔ No DOI found

The Salamanca Statement and Framework for Action on Special Needs Education - Spain. Ministerio de Educación y Ciencia (1994)

Social Network Analysis - Wasserman, S.; Faust, K. (1994)
Social network analysis is used widely in the social and behavioral sciences, as well as in economics, marketing, and industrial engineering. The social network perspective focuses on relationships among social entities and is an important addition to standard social and behavioral research, which is primarily concerned with attributes of the social units. Social Network Analysis: Methods and Applications reviews and discusses methods for the analysis of social networks with a focus on applications of these methods to many substantive examples. It is a reference book that can be used by those who want a comprehensive review of network methods, or by researchers who have gathered network data and want to find the most appropriate method by which to analyze it. It is also intended for use as a textbook as it is the first book to provide comprehensive coverage of the methodology and applications of the field.

General system theory: Toward a conceptual framework for science and technology education for all - Chen, David; Stroup, Walter (Journal of Science Education and Technology, 1993)
In this paper we suggest using general system theory (GST) as a unifying theoretical framework for science and technology education for all. Five reasons are articulated: the multidisciplinary nature of systems theory, the ability to engage complexity, the capacity to describe system dynamics and change, the ability to represent the relationship between the micro-level and macro-level of analysis, and the ability to bring together the natural and human worlds. The historical origins of system ideas are described, and the major concepts of system theory are mapped; including the mathematical, technological, and philosophical constructs. The various efforts to implement system thinking in educational contexts are reviewed, and three kinds of learning environments are defined: expert presentation, simulation, and real-world. A broad research agenda for exploring and drawing-out the educational implications of system thinking and learning is outlined. The study of both real-world and simulated learning environments is advocated.

Applying Systems Theory Through the Lens of Learning: What Does Learning Research Say? - Jones, Beau Fly; Knuth, Randy A.; Baxendale, Steve (Springer, 1993)
Two areas of learning research, research about the learning process and views about the learner, need to be considered to guide educational stakeholders in the task of successfully redesigning schools to promote learning. The most meaningful learning results from an instructional design based on learning research. Research in the application of systems theory in education has profound implications for curriculum, instruction, and assessment in schools.
Keywords: Affective education; IQ; cognitive theory; creative thinking; critical thinking; educational research; intelligence; learner; learning processes; learning strategies; learning theories; metacognition; multiple intelligences; schema theories; school restructuring

Resampling-based multiple testing: Examples and Methods for p-Value Adjustment - Westfall, Peter H; Young, S. Stanley (John Wiley & Sons, 1993)

How systems thinking applies to education. - Betts, Frank (Educational Leadership, 1992)
Keywords: ⛔ No DOI found

How Systems Thinking Applies to Education - Educational Leadership - Betts, Frank (1992)

Ecological systems theory. - Bronfenbrenner, Urie (Jessica Kingsley Publishers, 1992)

Hierarchical linear models: Applications and data analysis methods - Bryk, Anthony S.; Raudenbush, Stephen W. (Hierarchical linear models: Applications and data analysis methods, 1992)
Much social and behavioral research involves hierarchical data structures. . . . Recent developments in the statistical theory of hierarchical linear models now afford an integrated set of methods for such applications. This introductory text explicates the theory and use of hierarchical linear models (HLM) through rich, illustrative examples and lucid explanations. The presentation remains reasonably nontechnical by focusing on three general research purposes—improved estimation of effects within an individual unit, estimating and testing hypotheses about cross-level effects, and partitioning of variance and covariance components among levels. This innovative volume describes use of both two and three level models in organizational research, studies of individual development and meta-analysis applications, and concludes with a formal derivation of the statistical methods used in the book. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Mathematical Modeling; Statistical Analysis

BRIDGING COMMUNICATION BARRIERS TO EFFECTIVE TEACHING IN NIGERIAN LANGUAGES: THE ROLE OF EDUCATIONAL TECHNOLOGY - Educational, African; Nwosu, Theory Don (1992)
null

Fuzzy systems theory and its applications - Sugeno, Michio; Asai, K.; Terano, T. (Tokyo Institute of Technology, 1992)
Keywords: ⛔ No DOI found

Systems Design of Education: A Journey to Create the Future - Banathy, Bela H. (Educational Technology, 1991)
Keywords: Education / General

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberle (Stanford Law Review, 1991)

Constitution of Sierra Leone - Government of Sierra Leone (1991)

Situating learning in communities of practice. - Lave, Jean (Perspectives on socially shared cognition., 1991)

Approaches to qualitative-quantitative methodological triangulation - Morse, Janice M. (Nursing research, 1991)

The Reflective Practitioner: How Professionals Think. - Schön, D. A. (Arena, 1991)

Standards for Education Data Collection and Reporting - SEDCR (1991)

Operational definitions and learning disabilities: An overview - Swanson, H. Lee (Learning Disability Quarterly, 1991)
Keywords: ⛔ No INSPIRE recid found

Computer Aided Systems Theory-EUROCAST'89: A Selection of Papers from the International Workshop EUROCAST'89, Las Palmas, Spain, February 26-March 4, 1989. Proceedings - Pichler, Franz; Moreno-Diaz, Roberto (Springer Science & Business Media, 1990)